Implementation Of Society Technology (Science) Approach Through Experimental Methods In Physics Learning In Class VIII MTsN 4 Banda Aceh - Mahyana, Mahyana (Journal of Technology and Literacy in Education, 2022)
The aims of this study were (1) to find out how far students can master the concept of physics by implementing the Science Technology Society approach through the experimental method. (2) How is the teacher’s ability to manage learning with the Science Technology Community approach through the experimental method. This classroom action research was conducted in class VIII-1 MTsN 4 Banda Aceh with a total of 31 students, consisting of 12 boys and 19 girls. The conclusions that the authors can convey in this study are as follows (1) Learning using the Community Science and Technology Approach can improve student learning achievement in simple plane material at MTsN 4 Banda Aceh. This can be seen from the completeness individually starting from lesson plan 1 by 78% and lesson plan 2 by 85%, (2) the teacher’s ability to manage learning using the Science Technology Community approach during cycle 1 and cycle 2 has increased from the good category with an average score -average 3.2 being a very good category with an average value of 3.8.